2021
DOI: 10.1097/md.0000000000027311
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between smartphone use and dry eye disease

Abstract: Background: Emerging research findings suggest a potential relationship between smartphone use (SPU) and dry eye disease (DED), which has not been systematically reviewed.Objectives: The aim of this study was to systematically review and synthesize evidence on the relationship between SPU and DED.Methods: A systematic search of Medline, EMBASE, CINAHL, and PsychINFO bibliographic databases from their inception to January 15, 2021. Study screening, full-text assessment, study selection and exclusion, data extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…19,20 Similar to current study findings reports published by Choi et al and Al-Marri et al revealed that usage of smartphones for a prolonged period of time may also increase the incidence of dry eyes. 21,22 Thus results of current study reveals that Overuse of smart phones, tablets or computers increases the prevalence of dry eye which inturn affect their outdoor activity, studies and over all development of children.…”
Section: Discussionmentioning
confidence: 62%
“…19,20 Similar to current study findings reports published by Choi et al and Al-Marri et al revealed that usage of smartphones for a prolonged period of time may also increase the incidence of dry eyes. 21,22 Thus results of current study reveals that Overuse of smart phones, tablets or computers increases the prevalence of dry eye which inturn affect their outdoor activity, studies and over all development of children.…”
Section: Discussionmentioning
confidence: 62%
“…Isso sugere que o tempo prolongado gasto em telas digitais pode levar a uma diminuição da taxa de piscar, resultando em uma menor produção de lágrimas e, consequentemente, contribuindo para o desenvolvimento da doença do olho seco. (Al-Marri et. al., 2021).…”
Section: Resultsunclassified
“…O uso frequente de smartphones pode levar a uma exposição prolongada à luz azul emitida pelas telas dos dispositivos eletrônicos, que pode causar fadiga ocular, irritação e inflamação, todos os quais são fatores que contribuem para a progressão da doença do olho seco. (Al-Marri et. al., 2021).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Vitamin A plays a vital role in ocular function and is involved in preventing xerophthalmia, the maintenance of eye integrity, and cellular division and differentiation [ 3 , 4 , 5 ]. Recently, the global prevalence of dry eye disease (DED) has been estimated to be between 5% and 50% [ 6 ]. It was concluded from previous investigations that excessive smartphone use in children and adolescents is associated with DED [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%